PHYSICAL EXERCISE PROGRAM AND ITS EFFECTS ON CARDIORESPIRATORY CONDUCTION AND ON PSYCHOLOGICALSYMPTOMS ON PERIMENOPAUSAL WOMEN (Fiep Bulletin - online, 2014)
The aim of this study was to evaluate the responses of the cardiorespiratory condition and of the psychological symptoms in women on the perimenopausal phase, after making a 20 week training, with strength and aerobic (on a treadmill) exercises. The frequency was of 3 times a week. Two groups were tested: group GC (n10) women in perimenopause phase, with no training; group GE (n14) women in perimenopause phase, with training. Any of the groups made hormonal therapy during the study. Some statistically significant difference was noticed on VO2max ml/kg/min and on resting cardiac frequency (FCr) between groups GC and GE on the post-test. There was a statistically significant reduction in RQ in group GE. It was observed a statistically significant reduction in group GE on the symptom distress, irritability and anxiety. It was concluded that 20 weeks of training with exercises is time enough to promote raisings on VO2max, reductions on FCr and changes on QR; it is a possibility of therapy to help on the control of psychological symptoms during perimenopause.
Keywords: perimenopause; physical exercises; cardiorespiratory condition; psychological symptoms